2002
DOI: 10.1053/ejvs.2002.1598
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of MMP-2 and MMP-9 Leads to Degradation of Type IV Collagen During Skeletal Muscle Reperfusion Injury; Protection by the MMP Inhibitor, Doxycycline

Abstract: MMP-2 and MMP-9 are strongly upregulated in skeletal muscle ischaemia/reperfusion injury and are also upregulated in remote organs, leading to degradation of basement membranes. Inhibition of MMP activity may therefore be potentially therapeutically useful in reducing the severity of reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 40 publications
4
92
0
2
Order By: Relevance
“…Ischemia and reperfusion are recognized as being involved in both acute and chronic rejection [20]. Recent studies have reported that ischemia and reperfusion increase the expression and activity of MMP-2 and MMP-9 in rat muscle and lung, but not in the kidney [23,331. Thus, our results are in agreement with these studies and indicate that ischemia/ reperfusion did not contribute to the changes in MMP activity measured during acute rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia and reperfusion are recognized as being involved in both acute and chronic rejection [20]. Recent studies have reported that ischemia and reperfusion increase the expression and activity of MMP-2 and MMP-9 in rat muscle and lung, but not in the kidney [23,331. Thus, our results are in agreement with these studies and indicate that ischemia/ reperfusion did not contribute to the changes in MMP activity measured during acute rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of fluorescence was digitized and measured using Scion Image TM to compare the relative intensity of fluorescence between samples as described by Roach. 17 …”
Section: Immunohistochemistymentioning
confidence: 99%
“…In contrast, MMP-9 shows none or a very modest basal expression, but its promoter region contains a variety of response elements sensitive to a wide range of growth factors and cytokines (33). MMP-9 has been proposed to affect general collagen turnover in skeletal muscle and in vitro models of disease (7,9,28). It might also to be a regulator of growth factor bioavailability via proteolytic release (8,21).…”
mentioning
confidence: 99%
“…Physical exercise is a complex process constituting several factors that could affect the expression levels of MMP-2 and MMP-9 in skeletal muscle, such as local ischemia and increases in muscle stretching; in shear stress; and in the wall tension of blood vessels (2,24,28). Despite the established importance of ECM remodeling in the skeletal muscle during adaptation to exercise and the central role of MMPs in these processes, MMP levels in exercising skeletal muscle have been largely overlooked.…”
mentioning
confidence: 99%